2020
DOI: 10.31235/osf.io/kv8dg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changing living arrangements, family dynamics and stress during lockdown: evidence from four birth cohorts in the UK

Abstract: On 23 March 2020 the UK went into lockdown in an unprecedented step to attempt to limit the spread of coronavirus. Since then, many families have found themselves spending an unprecedented amount of time together, with some facing the additional challenge of adapting to changes in who they are living with as some families have found themselves unexpectedly brought back together. School and university closures, the move to remote working, furlough or the loss of employment have all meant that many adult childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
2
5
2
Order By: Relevance
“…With overcrowded housing increasing risk of COVID-19 transmission, disparities in housing disruption are likely to have impacts on risk of COVID-19 infection and other poor health and economic outcomes (36). Although there have been reported changes in individuals’ housing situations during the pandemic, with evidence of younger people moving themselves, and older adults having people move into their households (37), we find no associations in the risk of housing disruptions with prior mental health in this study. This finding might reflect policies that were designed to minimise home loss during the pandemic and these outcomes should be monitored in the medium and longer-term as consequences of the economic and health disruptions are realised and protective policies are lifted.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…With overcrowded housing increasing risk of COVID-19 transmission, disparities in housing disruption are likely to have impacts on risk of COVID-19 infection and other poor health and economic outcomes (36). Although there have been reported changes in individuals’ housing situations during the pandemic, with evidence of younger people moving themselves, and older adults having people move into their households (37), we find no associations in the risk of housing disruptions with prior mental health in this study. This finding might reflect policies that were designed to minimise home loss during the pandemic and these outcomes should be monitored in the medium and longer-term as consequences of the economic and health disruptions are realised and protective policies are lifted.…”
Section: Discussioncontrasting
confidence: 90%
“…The heightened risk for clusters of disruptions for those with psychological distress may be largely due to the increased risk of disruptions to healthcare, economic activity and income, as that combined with no difference in risk for housing disruptions will still mean clusters of disruptions are more likely. Furthermore, adverse outcomes may cluster, for example, with housing disruption resulting from employment loss, or those with poor mental health being more likely to experience healthcare disruptions as a result of moving home and general practice (37). Multiple adverse disruptions are also potentially stressful and more predictive of poorer prognosis longer-term (38).…”
Section: Discussionmentioning
confidence: 99%
“…Second, approximately only half of the eligible sample answered our survey. This is in line with cohorts in the UK and the Netherlands that presented response rates in online assessments during the pandemic of 25-55% (Pan et al, 2020;Pierce et al, 2020;Evandrou et al, 2021). These modest rates probably occurred due to the need of rapid organization for collecting timely data during the pandemic.…”
Section: Limitationssupporting
confidence: 72%
“…Furthermore, adverse outcomes may cluster; for example, with housing disruption resulting from employment loss, or those with poor mental health being more likely to experience healthcare disruptions as a result of moving home and general practice. 36 Multiple adverse disruptions are potentially predictive of poorer prognosis longer term. 37 We found that those with prior mental distress were more likely to suffer multiple disruptions, highlighting the need for inter-agency working in supporting those with mental ill health.…”
Section: Discussionmentioning
confidence: 99%